The Effectiveness of Health BPJS Claim Discrepancies Against Health Service Standards in Indonesia - Praja, Nucky Indra; Ferianasari, Ineke Winda; Jaqualina, Cornelia (President University, 2024)
This study aims to evaluate the effectiveness of the Badan Penyelenggara Jaminan Sosial (BPJS) health system in addressing claim discrepancies in relation to health service standards in Indonesia. As a social security administration agency, BPJS Health faces various challenges concerning claim discrepancies, which can impact the quality of healthcare services provided to the community. Health insurance claims refer to submissions made by healthcare facilities to BPJS for reimbursement of healthcare service costs. These claims are submitted collectively on a monthly basis, accompanied by supporting documents. Upon submission, the claims undergo a verification process conducted by BPJS Health verifiers, whose role is to assess the accuracy and completeness of the administrative accountability for services provided to patients. Following claim verification, the insurer at the healthcare facility receives one of four claim status outcomes: eligible claim status, ineligible claim status (pending), post-claim verification status, or disputed claim status. This study employs a normative juridical research method, involving the collection and analysis of primary, secondary, and tertiary legal materials. The findings reveal several factors contributing to claim discrepancies, including hospitals’ and healthcare professionals’ limited understanding of claim procedures, as well as inefficiencies in BPJS Health’s monitoring and evaluation system. The study also highlights that claim discrepancies often have a negative impact on patient satisfaction and the overall quality of healthcare services. To enhance the effectiveness of the BPJS Health claims system, improvements are needed, including systematic reforms, increased dissemination of information, targeted training programs for healthcare workers, and the strengthening of monitoring and evaluation mechanisms. These measures will contribute to improving the efficiency and reliability of healthcare services in Indonesia.